TAX AVOIDANCE AND EVASION IN THE DIGITAL ECONOMY: CHALLENGES AND SOLUTIONS - Judijanto, Loso (Accounting Studies and Tax Journal (COUNT), 2025)
The rapid development of the digital economy has fundamentally changed global business models, creating new challenges in taxation that affect tax compliance and tax avoidance in cross-border digital companies. This research aims to analyze the effectiveness of digital tax policies in suppressing tax avoidance and evasion practices through a Systematic Literature Review (SLR) approach. Using data from various leading academic sources, this research identifies digital tax policy trends, their impact on tax compliance, and the challenges faced in their implementation. The results show that although policies such as the Digital Services Tax (DST) and digital Value Added Tax (VAT) have the potential to increase tax revenues, they often face resistance from multinational companies and challenges in implementation in developing countries. This research recommends increasing international cooperation, transparency in tax reporting, and the use of advanced technology to increase the effectiveness of digital tax policies in the digital economy era.